Thermoplastic starch/talc bionanocomposites: Influence of particle morphology on final properties - Castillo, Luciana Andrea (2015)
This work analyzed the effect of talc morphology on structural characteristics and final properties of thermoplastic corn starch (TPS). In this sense, omposite films based on TPS containing talc nanoparticles were obtained by melt-mixing and thermo-compression. Talc samples with different morphological characteristics (platy-microcrystalline and blocky-macrocrystalline), derived from their formation process,were used. Platy and blocky morphology was distinguished by Scanning Electron Microscopy performed on composites films. Microcrystalline morphology induced smaller TPS crystallites thanmacrocrystalline one, indirectly evidenced by X-Ray Diffraction and Differential Scanning Calorimetry. Crystalline character of talc particles also affected visible and UV barrier capacity of TPS films. Blocky morphology of mineral filler led to the highest reduction of TPS water vapor permeation. Both talcsamples acted as matrix reinforcement agents. However, macrocrystalline articles induced the major changes on elastic modulus and tensile strength, without affecting films ductility.